Conditions of institutionalism application as a theoretical basis for economic analysis - I. A. Mankovsky (Вестник университета)
Russian society is a complex social system, the functioning of which is conditioned by socio-economic policy, the development process of which requires a comprehensive economic analysis of virtually all spheres of social interaction. The interdisciplinary scientific approach to economic analysis, which makes it possible to consider the impact on socio-economic development of various aspects of the state and society functioning, is inherent in institutional economic theory. However, the problem of its application to the Russian state and society analysis is that institutionalism developed by American scientists is based on analyzing the political and legal system of the United States of America, which differ significantly from the political and legal system of Russia. The purpose of the study is to determine the conditions for institutionalism application in the process of economic analysis of political and economic subsystems of Russian society and socio-economic policy development that meets the requirements of the time. The relevance of the study is conditioned by the impossibility of applying the neoclassical economic paradigm to conduct a comprehensive economic analysis of the social system, as well as by the institutionalism dynamic development, which applies an interdisciplinary approach to economic analysis. The study proposes measures aimed at adapting institutionalism to the conditions of Russia and its population development, formulates the author’s approach to the universal definition of its basic concepts. The study contributes to institutionalism development, promotes a unified institutional economic theory creation and the conditions for its application for the interdisciplinary economic analysis of various aspects of the Russian society development as a complex social system.